Caffeoylquinic Acid-Rich Extract of Aster glehni F. Schmidt Ameliorates Nonalcoholic Fatty Liver through the Regulation of PPARδ and Adiponectin in ApoE KO Mice. (23rd October 2017) - Lee, Yong-Jik; Jang, Yoo-Na; Han, Yoon-Mi; Kim, Hyun-Min; Jeong, Jong-Min; Son, Min Jeoung; Jin, Chang Bae; Kim, Hyoung Ja; Seo, Hong Seog
Abstract : Aster glehni is well known for its therapeutic properties. This study was performed to investigate the effects of A. glehni on nonalcoholic fatty liver disease (NAFLD) in atherosclerotic condition, by determining the levels of biomarkers related to lipid metabolism and inflammation in serum, liver, and adipose tissue. Body and abdominal adipose tissue weights and serum triglyceride level decreased in all groups treated with A. glehni . Serum adiponectin concentration and protein levels of peroxisome proliferator-activated receptor δ, 5′ adenosine monophosphate-activated protein kinase, acetyl-CoA carboxylase, superoxide dismutase, and PPAR γ coactivator 1-alpha in liver tissues increased in the groups treated with A. glehni . Conversely, protein levels of ATP citrate lyase, fatty acid synthase, tumor necrosis factor α, and 3-hydroxy-3-methylglutaryl-CoA reductase and the concentrations of interleukin 6 and reactive oxygen species decreased upon A. glehni . Triglyceride concentration in the liver was lower in mice treated with A. glehni than in control mice. Lipid accumulation in HepG2 and 3T3-L1 cells decreased upon A. glehni treatment; this effect was suppressed in the presence of the PPAR δ antagonist, GSK0660. Our findings suggest that A. glehni extracts may ameliorate NAFLD through regulation of PPAR δ, adiponectin, and the related subgenes.